William Faulkner and Contemporary Society: Exploring William Faulkner's portrayal of contemporary society (Journal of Advances and Scholarly Researches in Allied Education, 2011)
William Faulkner is one of the best social scientist. He has a mastery over the representation of the contemporary society in his literature. He wants to paint the picture of present dehumanized society, so in order to give more clarity to his view point, he creates the imaginary primitive society, lived in a golden age, for comparison, but it is the present which is the focal point. As the bitter winter is compared with the memory of the bright gay summer, full of care and comfort and enjoyment, likewise the present Chaos is compared with the order of the golden past. And, as the ritual action assures the return of fertility of the earth, so the ritual actions can restore cosmos to the Chaos of the present. If we endure the normality of sufferings we will gain patience to forbear the hardships, so the reading of moral history is insisted upon.